Lady and the Tramp [videorecording (Blu-Ray + DVD)] - Penner, Erdman; Rinaldi, Joe; Wright, Ralph, 1908-1983; DaGradi, Don; Luske, Hamilton S.; Geronimi, Clyde; Jackson, Wilfred; Greene, Ward, 1892-1956 (Walt Disney signature collection., 2018)
A pedigreed cocker spaniel falls for the romance of a carefree mongrel, who helps her in her time of need.